2007
DOI: 10.1029/2007jb005061
|View full text |Cite
|
Sign up to set email alerts
|

Current deformation in the northern Canadian Cordillera inferred from GPS measurements

Abstract: Continuous and campaign‐style Global Positioning System (GPS) measurements provide new constraints on the first‐order current deformation pattern of the northern Cordillera of NW Canada and eastern Alaska. The Yakutat block is currently colliding with North America in the corner of the Gulf of Alaska. Our data infer that relative Yakutat–North America motion is accommodated across the eastern boundary by right‐lateral motion (∼40 mm/a), mainly on the Fairweather fault, and minor shortening (∼6 mm/a). To the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 50 publications
4
87
0
Order By: Relevance
“…[83] McKenzie Mountains (Canada) (MKM): From sparse continuously recording GPS measurements at sites SW of the mountains, Leonard et al [2007] reported a rate of convergence between them and North America of 3-10 mm/a, little different from $5 mm/yr given by Mazzotti and Hyndman [2002]. The wide range of possible rates derives in part from inconsistent velocities of campaign-style GPS measurements.…”
Section: à42mentioning
confidence: 99%
See 1 more Smart Citation
“…[83] McKenzie Mountains (Canada) (MKM): From sparse continuously recording GPS measurements at sites SW of the mountains, Leonard et al [2007] reported a rate of convergence between them and North America of 3-10 mm/a, little different from $5 mm/yr given by Mazzotti and Hyndman [2002]. The wide range of possible rates derives in part from inconsistent velocities of campaign-style GPS measurements.…”
Section: à42mentioning
confidence: 99%
“…Using seismic moments of moderate earthquakes, Leonard et al [2008] inferred rates of 1.8 to 4.0 mm/yr. Recognizing the large uncertainties associated with such estimates, we use a rate at the low end of what Leonard et al [2007] suggested: 5 AE 2 mm/yr.…”
Section: à42mentioning
confidence: 99%
“…Data time spans vary from 1992 to 2008, with an average time series length of 5-6 years. Details of the regional network processing are given in Mazzotti et al [2003b] and Leonard et al [2007]. The various networks are combined, aligned to the International Terrestrial Reference Frame ITRF2000, and referenced to stable North America using the North America/ITRF2000 rigid rotation [cf.…”
Section: Gps Data and Strain Ratesmentioning
confidence: 99%
“…It comprises 179 horizontal velocity vectors derived from 89 continuous and 90 campaign GPS stations throughout Alberta, British Columbia, and northern Washington [Henton et al, 2006;Leonard et al, 2007;Mazzotti et al, 2003aMazzotti et al, , 2003b] (see auxiliary material). Data time spans vary from 1992 to 2008, with an average time series length of 5-6 years.…”
Section: Gps Data and Strain Ratesmentioning
confidence: 99%
“…3). This oblique collision appears to be transferring strain to the north and northeast, causing active deformation across the Richardson and Mackenzie mountains (Mazzotti and Hyndman 2002;Leonard et al 2007;Leonard et al 2008). One intriguing question is to what extent the strain transfer occurs diffusely across hundreds of kilometres, as opposed to being accommodated by rigid blocks and a few discrete faults.…”
Section: Summary Of White Papersmentioning
confidence: 99%